THE EFFECTS OF ALPHA LIPOIC ACID ON LENS INJURY IN RATS ADMINISTERED WITH VALPROIC ACID - Yeşim Öztaylan; İsmet Burcu Türkyılmaz; Refiye Yanardağ (İstanbul Tıp Fakültesi Dergisi)
Objective: Valproic acid (2-propyl valeric acid; VPA) is an effective short-chained fatty acid which is used for the treatment of migraine and schizophrenia. Though it provides effective treatment, its side effects are associated with free radicals and in this way it affects many organs and tissues. Alpha lipoic acid (ALA) is known to be a powerful antioxidant. Material and Methods: The aim of this current study was to investigate the protection of ALA on VPA induced lens injury. Female rats were split into four groups as follows: 1st group, control animals (corn oil per day for 15 days); 2nd group, ALA administered group (50 mg per kg each day for 15 days); 3rd group, VPA administered group (500 mg per kg each day for 15 days) and 4th group, VPA and ALA administered group to which the same dose was given at the same time each day. On the 16th day, lens tissues were taken. Results: Lens glutathione levels and glutathione-S-transferase activities were decreased while lipid peroxidation and protein carbonyl levels, superoxide dismutase, glutathione peroxidase and reductase, aldose reductase and sorbitol dehydrogenase activities were elevated after VPA administration. ALA reversed these levels and activities in the VPA group. Conclusion: We can conclude that ALA used its antioxidant property and ameliorated VPA induced lens injury.